Acute thermal stress alters sperm swimming activity, viability, and gene expression in blue catfish, Ictalurus furcatus - Kaylan M. Price; Brian G. Bosworth; Samitha S.N. Liyanage; Jason W. Abernathy; Benjamin H. Beck; Luke A. Roy; Timothy J. Bruce; Rex A. Dunham; Ian A.E. Butts (Theriogenology, 2026)

Effect of short-term storage on sperm quality and microbiome dynamics in blue catfish, Ictalurus furcatus - Samitha S.N. Liyanage; Kasun A. Bandara; Kaylan A. Martin; Kyle R. Wood; Jason W. Abernathy; Benjamin H. Beck; Timothy J. Bruce; Luke A. Roy; Rex A. Dunham; Xu Wang; Ian A.E. Butts (Aquaculture, 2026)

Cryopreservation techniques for blue catfish, Ictalurus furcatus, sperm using 2.5 mL straws - Kyle R. Wood; Brian Bosworth; Samitha S.N. Liyanage; Alexandra E. Nowicki; Kaylan A. Martin; Rex A. Dunham; Benjamin H. Beck; Jason W. Abernathy; Xu Wang; Luke A. Roy; Ian A.E. Butts (Cryobiology, 2025)

Population Genomics Reveals Local Adaptation Related to Temperature Variation in Two Stream Frog Species: Implications for Vulnerability to Climate Warming - Brenna R. Forester; Amanda S. Cicchino; Alisha A. Shah; Austin B. Mudd; Eric C. Anderson; Jessen V. Bredeson; Andrew J. Crawford; Jason B. Dunham; Cameron K. Ghalambor; Erin L. Landguth; Brent W. Murray; Daniel Rokhsar; et al. (Molecular Ecology, 2025)
Identifying populations at highest risk from climate change is a critical component of conservation efforts. However, vulnerability assessments are usually applied at the species level, even though intraspecific variation in exposure, sensitivity and adaptive capacity play a crucial role in determining vulnerability. Genomic data can inform intraspecific vulnerability by identifying signatures of local adaptation that reflect population‐level variation in sensitivity and adaptive capacity. Here, we address the question of local adaptation to temperature and the genetic basis of thermal tolerance in two stream frogs ( Ascaphus truei and A. montanus ). Building on previous physiological and temperature data, we used whole‐genome resequencing of tadpoles from four sites spanning temperature gradients in each species to test for signatures of local adaptation. To support these analyses, we developed the first annotated reference genome for A. truei . We then expanded the geographic scope of our analysis using targeted capture at an additional 11 sites per species. We found evidence of local adaptation to temperature based on physiological and genomic data in A. montanus and genomic data in A. truei , suggesting similar levels of sensitivity (i.e., susceptibility) among populations regardless of stream temperature. However, invariant thermal tolerances across temperatures in A. truei suggest that populations occupying warmer streams may be most sensitive. We identified high levels of evolutionary potential in both species based on genomic and physiological data. While further integration of these data is needed to comprehensively evaluate spatial variation in vulnerability, this work illustrates the value of genomics in identifying spatial patterns of climate change vulnerability.

Parental impacts on industry-relevant offspring performance traits using blue catfish, Ictalurus furcatus (Valenciennes, 1840), cryopreserved sperm - Kyle R. Wood; Ying Zhang; V. MacKenzie Tackett; Kaylan A. Martin; Samitha S.N. Liyanage; Benjamin H. Beck; Jason W. Abernathy; Rex A. Dunham; Luke A. Roy; Xu Wang; Ian A.E. Butts (Theriogenology, 2025)

Sperm fatty acid composition as an indicator of quality and cryotolerance in blue catfish, Ictalurus furcatus - Kyle R. Wood; Matthew K. Litvak; Samitha S.N. Liyanage; Kaylan A. Martin; V. MacKenzie Tackett; Rex A. Dunham; Luke A. Roy; Cynthia K. Faulk; Benjamin H. Beck; Jason W. Abernathy; Xu Wang; Ian A.E. Butts (Theriogenology, 2025)

Linking Fire, Food Webs, and Fish in Stream Ecosystems - David A. Roon; J. Ryan Bellmore; Joseph R. Benjamin; François-Nicolas Robinne; Rebecca L. Flitcroft; Jana E. Compton; Joseph L. Ebersole; Jason B. Dunham; Kevin D. Bladon (Ecosystems, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The past, present, and a future for native charr in Japan - Kurt D. Fausch; Kentaro Morita; Jun-ichi Tsuboi; Yoichiro Kanno; Shoichiro Yamamoto; Daisuke Kishi; Jason B. Dunham; Itsuro Koizumi; Koh Hasegawa; Mikio Inoue; Takuya Sato; Satoshi Kitano (Ichthyological Research, 2024)
Charrs ( Salvelinus ) reach their southernmost distribution in Japan, and are uniquely adapted to the short, steep streams of this island archipelago. Southern Asian Dolly Varden ( Salvelinus curilus ) occur only in Hokkaido Island, whereas white-spotted charr ( Salvelinus leucomaenis ) range to southern Honshu. Both species diverged from an ancestral lineage during the late Pliocene/early Pleistocene, when lowered sea levels created semi-enclosed water bodies in the seas of Japan and Okhotsk. Genetic analyses showed S. curilus represents the most ancient divergence from the Dolly Varden ( Salvelinus malma ) - Arctic charr ( Salvelinus alpinus ) group, and revealed five lineages of S. leucomaenis which align differently than traditional subspecies. Japanese charr display diverse and flexible life histories including anadromous fish with partial migration, and fluvial, adfluvial, and resident forms. In Hokkaido, Dolly Varden are distributed upstream and white-spotted charr downstream. They coexist in narrow sympatric zones through adaptive shifts by Dolly Varden in behavior and morphology that facilitate benthic foraging. Both species hybridize with native and nonnative salmonids, and are displaced from microhabitats and decline in abundance when rainbow trout ( Oncorhynchus mykiss ) and brown trout ( Salmo trutta ) invade. Japan streams contain over 95,000 erosion control dams which create short stream fragments (medians ~200 m). This has increased extirpation of charr populations via lower genetic diversity and stochastic and demographic factors. Tributaries provide complex rearing habitats, afford refuges from floods, and supply recruits that sustain populations in mainstem fragments and create metapopulations in connected riverscapes. Charr play central roles in linked stream-riparian food webs, and cause direct and indirect effects that cascade to streambed algae and riparian predators when linkages are disrupted by anthropogenic effects or altered by native parasites. Many charr populations are threatened by habitat fragmentation and introgression or invasion by nonnative forms, but efforts to conserve charr are growing. These include restoring connectivity among pure populations above barriers that prevent invasions, protecting tributary nurseries, and instituting angling regulations to protect headwater populations. Key steps include inventorying pure populations, identifying conservation units, selecting appropriate management based on connectivity and biotic interactions, and engaging stakeholders and youth to engender an ethic for conserving irreplaceable charr lineages.

Co-production of models to evaluate conservation alternatives for a threatened fish in a rapidly changing landscape - Joseph R. Benjamin; Jason B. Dunham; Nolan P. Banish; David K. Hering; Zachary Tiemann (Aquatic Sciences, 2024)
Reintroductions are one means of managing species distributions, but the feasibility of such efforts is uncertain. Here we consider reintroduction for threatened bull trout ( Salvelinus confluentus ) that currently occupy a small fraction of historically occupied habitats in the upper Klamath River basin owing to climate warming and human modifications of ecosystems. We engaged stakeholders across multiple organizations to co-produce a decision support model that estimated the potential of reintroduction to establish new populations and persistence of donor populations. Stakeholders identified recipient and donor populations, strategy (e.g., artificial propagation, translocation), number of individuals, and life stage of bull trout. The most optimal decision for reintroduction was artificial propagation of 10,000 fry into Annie Creek. This strategy may have negative consequences on donor populations, with the exception of Sun Creek, which was resilient to simulated removal of bull trout. Donor populations and recipient streams identified as most feasible were generally consistent across all of these scenarios. During model development, however, an unexpected and intense wildfire affected half of the streams considered and may have dramatically impacted donor populations. With models in hand from the initial feasibility assessment, we adapted them to further evaluate the potential of supplementation following this massive disturbance. Overall, results of this study indicate the value of developing co-produced tools that can be rapidly adapted to evaluate the consequences of whole-system transformations in near-real-time assessments.

Estimating streamflow permanence with the watershed Erosion Prediction Project Model: Implications for surface water presence modeling and data collection - Konrad C. Hafen; Kyle Blasch; Paul E. Gessler; Jason Dunham; Erin Brooks (Journal of Hydrology, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Resist, accept, and direct responses to biological invasions: A social–ecological perspective - Jason Dunham; Joseph R. Benjamin; David J. Lawrence; Katherine Clifford (Fisheries Management and Ecology, 2022)
Biological invasions represent an important and unique case of ecological transformation that can strongly influence species and entire ecosystems. Challenges in managing invasions arise on multiple fronts, ranging from diverse and often divergent values associated with native and introduced species, logistical constraints, and transformation via other change agents (e.g., climate and land‐use change). We address biological invasions considering the Resist‐Accept‐Direct (RAD) framework for addressing ecological transformation. Because RAD is focused on decisions, we address both social and ecological factors that influence preferences for decision alternatives. We address social factors first as these can constrain the range of alternatives considered in an ecological context. Next, we address ecological dynamics by modeling trajectories from RAD alternatives in a two‐species scenario involving impacts of introduced brook trout ( Salvelinus fontinalis ) on native bull trout ( S. confluentus ). Results reveal that decision alternatives aligned with each of the major components of RAD can produce positive outcomes. In a management context, these findings highlight the value of investing in early engagement to fully identify decision alternatives, formalizing models of system dynamics to understand ecological trajectories, and applying this knowledge to set the stage for longer term efforts to address biological invasions.

Evaluating Coexistence of Fish Species with Coastal Cutthroat Trout in Low Order Streams of Western Oregon and Washington, USA - Kyle D. Martens; Jason Dunham (Fishes, 2021)
When multiple species of fish coexist there are a host of potential ways through which they may interact, yet there is often a strong focus on studies of single species without considering these interactions. For example, many studies of forestry–stream interactions in the Pacific Northwest have focused solely on the most prevalent species: Coastal cutthroat trout. To examine the potential for interactions of other fishes with coastal cutthroat trout, we conducted an analysis of 281 sites in low order streams located on Washington’s Olympic Peninsula and along the central Oregon coast. Coastal cutthroat trout and juvenile coho salmon were the most commonly found salmonid species within these streams and exhibited positive associations with each other for both presence and density. Steelhead were negatively associated with the presence of coastal cutthroat trout as well as with coho salmon and sculpins (Cottidae). Coastal cutthroat trout most frequently shared streams with juvenile coho salmon. For densities of these co-occurring species, associations between these two species were relatively weak compared to the strong influences of physical stream conditions (size and gradient), suggesting that physical conditions may have more of an influence on density than species interactions. Collectively, our analysis, along with a review of findings from prior field and laboratory studies, suggests that the net effect of interactions between coastal cutthroat trout and coho salmon do not appear to inhibit their presence or densities in small streams along the Pacific Northwest.

Application of multiple‐population viability analysis to evaluate species recovery alternatives - Helen M. Neville; Douglas R. Leasure; Daniel C. Dauwalter; Jason B. Dunham; Robin Bjork; Kurt A. Fesenmyer; Nathan D. Chelgren; Mary M. Peacock; Charles H. Luce; Daniel J. Isaak; Lee Ann Carranza; Jon Sjoberg; et al. (Conservation Biology, 2020)
Population viability analysis (PVA) is a powerful conservation tool, but it remains impractical for many species, particularly species with multiple, broadly distributed populations for which collecting suitable data can be challenging. A recently developed method of multiple‐population viability analysis (MPVA), however, addresses many limitations of traditional PVA. We built on previous development of MPVA for Lahontan cutthroat trout (LCT) ( Oncorhynchus clarkii henshawi ), a species listed under the U.S. Endangered Species Act, that is distributed broadly across habitat fragments in the Great Basin (U.S.A.). We simulated potential management scenarios and assessed their effects on population sizes and extinction risks in 211 streams, where LCT exist or may be reintroduced. Conservation populations (those managed for recovery) tended to have lower extinction risks than nonconservation populations (mean = 19.8% vs. 52.7%), but not always. Active management or reprioritization may be warranted in some cases. Eliminating non‐native trout had a strong positive effect on overall carrying capacities for LCT populations but often did not translate into lower extinction risks unless simulations also reduced associated stochasticity (to the mean for populations without non‐native trout). Sixty fish or 5–10 fish/km was the minimum reintroduction number and density, respectively, that provided near‐maximum reintroduction success. This modeling framework provided crucial insights and empirical justification for conservation planning and specific adaptive management actions for this threatened species. More broadly, MPVA is applicable to a wide range of species exhibiting geographic rarity and limited availability of abundance data and greatly extends the potential use of empirical PVA for conservation assessment and planning.

Modeling control of Common Carp (Cyprinus carpio) in a shallow lake–wetland system - James Pearson; Jason Dunham; J. Ryan Bellmore; Don Lyons (Wetlands Ecology and Management, 2019)

Hierarchical multi‐population viability analysis - Douglas R. Leasure; Seth J. Wenger; Nathan D. Chelgren; Helen M. Neville; Daniel C. Dauwalter; Robin Bjork; Kurt A. Fesenmyer; Jason B. Dunham; Mary M. Peacock; Charlie H. Luce; Abby C. Lute; Daniel J. Isaak (Ecology, 2019)
Population viability analysis ( PVA ) uses concepts from theoretical ecology to provide a powerful tool for quantitative estimates of population dynamics and extinction risks. However, conventional statistical PVA requires long‐term data from every population of interest, whereas many species of concern exist in multiple isolated populations that are only monitored occasionally. We present a hierarchical multi‐population viability analysis model that increases inference power from sparse data by sharing information among populations to assess extinction risks while accounting for incomplete detection and sampling biases with explicit observation and sampling sub‐models. We present a case study in which we customized this model for historical population monitoring data (1985–2015) from federally threatened Lahontan cutthroat trout populations in the Great Basin, USA . Data were counts of fish captured during backpack electrofishing surveys from locations associated with 155 isolated populations. Some surveys (25%) included multi‐pass removal sampling, which provided valuable information about capture efficiency. GIS and remote sensing were used to estimate August stream temperatures, peak flows, and riparian vegetation condition in each population each year. Field data were used to derive an annual index of nonnative trout densities. Results indicated that population growth rates were higher in colder streams and that nonnative trout reduced carrying capacities of native trout. Extinction risks increased with more environmental stochasticity and were also related to population extent, water temperatures, and nonnative densities. We developed a graphical user interface to interact with the fitted model results and to simulate future habitat scenarios and management actions to assess their influence on extinction risks in each population. Hierarchical multi‐population viability analysis bridges the gap between site‐level field observations and population‐level processes, making effective use of existing datasets to support management decisions with robust estimates of population dynamics, extinction risks, and uncertainties.

Rising synchrony controls western North American ecosystems - Bryan A. Black; Peter van der Sleen; Emanuele Di Lorenzo; Daniel Griffin; William J. Sydeman; Jason B. Dunham; Ryan R. Rykaczewski; Marisol García‐Reyes; Mohammad Safeeq; Ivan Arismendi; Steven J. Bograd (Global Change Biology, 2018)
Along the western margin of North America, the winter expression of the North Pacific High (NPH) strongly influences interannual variability in coastal upwelling, storm track position, precipitation, and river discharge. Coherence among these factors induces covariance among physical and biological processes across adjacent marine and terrestrial ecosystems. Here, we show that over the past century the degree and spatial extent of this covariance (synchrony) has substantially increased, and is coincident with rising variance in the winter NPH. Furthermore, centuries‐long blue oak ( Quercus douglasii ) growth chronologies sensitive to the winter NPH provide robust evidence that modern levels of synchrony are among the highest observed in the context of the last 250 years. These trends may ultimately be linked to changing impacts of the El Niño Southern Oscillation on midlatitude ecosystems of North America. Such a rise in synchrony may destabilize ecosystems, expose populations to higher risks of extinction, and is thus a concern given the broad biological relevance of winter climate to biological systems.

Survey of Beaver-related Restoration Practices in Rangeland Streams of the Western USA - David S. Pilliod; Ashley T. Rohde; Susan Charnley; Rachael R. Davee; Jason B. Dunham; Hannah Gosnell; Gordon E. Grant; Mark B. Hausner; Justin L. Huntington; Caroline Nash (Environmental Management, 2018)

Aquatic biodiversity in forests: a weak link in ecosystem services resilience - Brooke E. Penaluna; Deanna H. Olson; Rebecca L. Flitcroft; Matthew A. Weber; J. Ryan Bellmore; Steven M. Wondzell; Jason B. Dunham; Sherri L. Johnson; Gordon H. Reeves (Biodiversity and Conservation, 2017)

Impacts of climatic variation on trout: a global synthesis and path forward - Ryan P. Kovach; Clint C. Muhlfeld; Robert Al-Chokhachy; Jason B. Dunham; Benjamin H. Letcher; Jeffrey L. Kershner (Reviews in Fish Biology and Fisheries, 2016)

Genetic signatures of historical dispersal of fish threatened by biological invasions: the case of galaxiids in South America - Delphine Vanhaecke; Carlos Garcia de Leaniz; Gonzalo Gajardo; Jason Dunham; Guillermo Giannico; Sofia Consuegra (Journal of Biogeography, 2015)
Aim The ecological effects of biological invasions are well documented, but little is known about the effects of invaders on the genetic structure of native species. We examined the phylogeography, genetic variation and population structuring of two galaxiid fishes, Aplochiton zebra and A. taeniatus , threatened by non‐native salmonids, and whose conservation is complicated by misidentification and limited knowledge of their genetic diversity. Location Chile and the Falkland Islands. Methods We combined microsatellite and mitochondrial DNA (16S rDNA and COI ) markers to compare genetic diversity, effective population size and gene flow of Aplochiton spp. populations differentially affected by salmonid presence. Results We identified two 16S rDNA haplotypes among A. zebra – one dominant in coastal populations and another dominant in inland populations. Populations living on the island of Chiloé displayed a mixture of coastal and inland haplotypes, as well as high microsatellite diversity, as one would expect if the island had been a refugium during the Last Glacial Maximum, or a contact zone among populations. Microsatellite data revealed strong population structuring, indicative of current isolation patterns, and a negative correlation between the genetic diversity of A. zebra and the relative abundance of invasive salmonids. Main conclusions Our study indicates that population structuring of A. zebra reflects the influence of historical patterns of migration, but also the current levels of reduced gene flow among watersheds. Invasive salmonids, known to compete with and prey on native galaxiids, may have had negative impacts on the genetic diversity of Aplochiton spp. The low genetic variation found in some populations, coupled with potential biases in abundance estimates due to species misidentification, highlight the urgent need for more research into the conservation status of the two species of Aplochiton .

Long‐term growth‐increment chronologies reveal diverse influences of climate forcing on freshwater and forest biota in the Pacific Northwest - Bryan A. Black; Jason B. Dunham; Brett W. Blundon; Jayne Brim‐Box; Alan J. Tepley (Global Change Biology, 2015)
Analyses of how organisms are likely to respond to a changing climate have focused largely on the direct effects of warming temperatures, though changes in other variables may also be important, particularly the amount and timing of precipitation. Here, we develop a network of eight growth‐increment width chronologies for freshwater mussel species in the Pacific Northwest, United States and integrate them with tree‐ring data to evaluate how terrestrial and aquatic indicators respond to hydroclimatic variability, including river discharge and precipitation. Annual discharge averaged across water years (October 1–September 30) was highly synchronous among river systems and imparted a coherent pattern among mussel chronologies. The leading principal component of the five longest mussel chronologies (1982–2003; PC 1 mussel ) accounted for 47% of the dataset variability and negatively correlated with the leading principal component of river discharge ( PC 1 discharge ; r = −0.88; P PC 1 mussel and PC 1 discharge were closely linked to regional wintertime precipitation patterns across the Pacific Northwest, the season in which the vast majority of annual precipitation arrives. Mussel growth was also indirectly related to tree radial growth, though the nature of the relationships varied across the landscape. Negative correlations occurred in forests where tree growth tends to be limited by drought while positive correlations occurred in forests where tree growth tends to be limited by deep or lingering snowpack. Overall, this diverse assemblage of chronologies illustrates the importance of winter precipitation to terrestrial and freshwater ecosystems and suggests that a complexity of climate responses must be considered when estimating the biological impacts of climate variability and change.

Erratum to: Ecological and evolutionary patterns of freshwater maturation in Pacific and Atlantic salmonines - Matthew R. Sloat; Dylan J. Fraser; Jason B. Dunham; Jeffrey A. Falke; Chris E. Jordan; John R. McMillan; Haley A. Ohms (Reviews in Fish Biology and Fisheries, 2014)

Differential invasion success of salmonids in southern Chile: patterns and hypotheses - Ivan Arismendi; Brooke E. Penaluna; Jason B. Dunham; Carlos García de Leaniz; Doris Soto; Ian A. Fleming; Daniel Gomez-Uchida; Gonzalo Gajardo; Pamela V. Vargas; Jorge León-Muñoz (Reviews in Fish Biology and Fisheries, 2014)

Ecological and evolutionary patterns of freshwater maturation in Pacific and Atlantic salmonines - Matthew R. Sloat; Dylan J. Fraser; Jason B. Dunham; Jeffrey A. Falke; Chris E. Jordan; John R. McMillan; Haley A. Ohms (Reviews in Fish Biology and Fisheries, 2014)

Environmental flows: a definitive guide - Jason B. Dunham (Environmental Biology of Fishes, 2014)

Probabilistic accounting of uncertainty in forecasts of species distributions under climate change - Seth J. Wenger; Nicholas A. Som; Daniel C. Dauwalter; Daniel J. Isaak; Helen M. Neville; Charles H. Luce; Jason B. Dunham; Michael K. Young; Kurt D. Fausch; Bruce E. Rieman (Global Change Biology, 2013)
Forecasts of species distributions under future climates are inherently uncertain, but there have been few attempts to describe this uncertainty comprehensively in a probabilistic manner. We developed a Monte Carlo approach that accounts for uncertainty within generalized linear regression models (parameter uncertainty and residual error), uncertainty among competing models (model uncertainty), and uncertainty in future climate conditions (climate uncertainty) to produce site‐specific frequency distributions of occurrence probabilities across a species' range. We illustrated the method by forecasting suitable habitat for bull trout ( Salvelinus confluentus ) in the Interior Columbia River Basin, USA , under recent and projected 2040s and 2080s climate conditions. The 95% interval of total suitable habitat under recent conditions was estimated at 30.1–42.5 thousand km; this was predicted to decline to 0.5–7.9 thousand km by the 2080s. Projections for the 2080s showed that the great majority of stream segments would be unsuitable with high certainty, regardless of the climate data set or bull trout model employed. The largest contributor to uncertainty in total suitable habitat was climate uncertainty, followed by parameter uncertainty and model uncertainty. Our approach makes it possible to calculate a full distribution of possible outcomes for a species, and permits ready graphical display of uncertainty for individual locations and of total habitat.

Increasing synchrony of high temperature and low flow in western North American streams: double trouble for coldwater biota? - Ivan Arismendi; Mohammad Safeeq; Sherri L. Johnson; Jason B. Dunham; Roy Haggerty (Hydrobiologia, 2013)

Variability in expression of anadromy by female Oncorhynchus mykiss within a river network - Justin S. Mills; Jason B. Dunham; Gordon H. Reeves; John R. McMillan; Christian E. Zimmerman; Chris E. Jordan (Environmental Biology of Fishes, 2012)

Individual condition and stream temperature influence early maturation of rainbow and steelhead trout, Oncorhynchus mykiss - John R. McMillan; Jason B. Dunham; Gordon H. Reeves; Justin S. Mills; Chris E. Jordan (Environmental Biology of Fishes, 2012)

Threatened fishes of the world: Salvelinus confluentus (Salmoninae) - Eva Schemmel; Jason Dunham (Environmental Biology of Fishes, 2010)

Invasion versus Isolation: Trade‐Offs in Managing Native Salmonids with Barriers to Upstream Movement - KURT D. FAUSCH; BRUCE E. RIEMAN; JASON B. DUNHAM; MICHAEL K. YOUNG; DOUGLAS P. PETERSON (Conservation Biology, 2009)
Conservation biologists often face the trade‐off that increasing connectivity in fragmented landscapes to reduce extinction risk of native species can foster invasion by non‐native species that enter via the corridors created, which can then increase extinction risk. This dilemma is acute for stream fishes, especially native salmonids, because their populations are frequently relegated to fragments of headwater habitat threatened by invasion from downstream by 3 cosmopolitan non‐native salmonids. Managers often block these upstream invasions with movement barriers, but isolation of native salmonids in small headwater streams can increase the threat of local extinction. We propose a conceptual framework to address this worldwide problem that focuses on 4 main questions. First, are populations of conservation value present (considering evolutionary legacies, ecological functions, and socioeconomic benefits as distinct values)? Second, are populations vulnerable to invasion and displacement by non‐native salmonids? Third, would these populations be threatened with local extinction if isolated with barriers? And, fourth, how should management be prioritized among multiple populations? We also developed a conceptual model of the joint trade‐off of invasion and isolation threats that considers the opportunities for managers to make strategic decisions. We illustrated use of this framework in an analysis of the invasion‐isolation trade‐off for native cutthroat trout (Oncorhynchus clarkii) in 2 contrasting basins in western North America where invasion and isolation are either present and strong or farther away and apparently weak. These cases demonstrate that decisions to install or remove barriers to conserve native salmonids are often complex and depend on conservation values, environmental context (which influences the threat of invasion and isolation), and additional socioeconomic factors. Explicit analysis with tools such as those we propose can help managers make sound decisions in such complex circumstances.

Influences of Wildfire and Channel Reorganization on Spatial and Temporal Variation in Stream Temperature and the Distribution of Fish and Amphibians - Jason B. Dunham; Amanda E. Rosenberger; Charlie H. Luce; Bruce E. Rieman (Ecosystems, 2007)

Microsatellite variation reveals weak genetic structure and retention of genetic variability in threatened Chinook salmon (Oncorhynchus tshawytscha) within a Snake River watershed - Helen Neville; Daniel Isaak; Russell Thurow; Jason Dunham; Bruce Rieman (Conservation Genetics, 2006)

Combining Inferences from Models of Capture Efficiency, Detectability, and Suitable Habitat to Classify Landscapes for Conservation of Threatened Bull Trout - James T. Peterson; Jason Dunham (Conservation Biology, 2003)
Effective conservation efforts for at‐risk species require knowledge of the locations of existing populations. Species presence can be estimated directly by conducting field‐sampling surveys or alternatively by developing predictive models. Direct surveys can be expensive and inefficient, particularly for rare and difficult‐to‐sample species, and models of species presence may produce biased predictions. We present a Bayesian approach that combines sampling and model‐based inferences for estimating species presence. The accuracy and cost‐effectiveness of this approach were compared to those of sampling surveys and predictive models for estimating the presence of the threatened bull trout ( Salvelinus confluentus ) via simulation with existing models and empirical sampling data. Simulations indicated that a sampling‐only approach would be the most effective and would result in the lowest presence and absence misclassification error rates for three thresholds of detection probability. When sampling effort was considered, however, the combined approach resulted in the lowest error rates per unit of sampling effort. Hence, lower probability‐of‐detection thresholds can be specified with the combined approach, resulting in lower misclassification error rates and improved cost‐effectiveness.

Alien invasions in aquatic ecosystems: Toward an understanding of brook trout invasions and potential impacts on inland cutthroat trout in western North America - Jason B. Dunham; Susan B. Adams; Robert E. Schroeter; Douglas C. Novinger (Reviews in Fish Biology and Fisheries, 2002)

DIET OF GRAY WHALES ( ESCHRICHTIUS ROBUSTUS ) IN CLAYOQUOT SOUND, BRITISH COLUMBIA, CANADA - Jason S. Dunham; David A. Duffus (Marine Mammal Science, 2002)
A bstract In Clayoquot Sound, British Columbia, gray whales ( Eschrichtius robustus ) forage for pelagic, hyperbenthic, and benthic invertebrates. Prey types were collected near feeding whales and at sites where no whales were observed to ascertain whales' diets and to describe prey populations and distributions. Characteristics of prey that are examined include species composition, density, biomass, and size. Whales foraged for mysids, Holmesimysis sculpta being the most abundant species collected. Whales foraged near concentrated patches of porcelain crab zoeal larvae, composed primarily of Pachycheles rudis , 21 –294 times the average density and biomass normally collected. Amphipod biomass, composed primarily of Ampelisca agassizi and A. careyi , was 160 ± 150 g/m 2 where whales foraged. Larger amphipods, rather than higher density, resulted in higher amphipod biomass between years. Whales foraged where there was a high proportion (61%) of amphipods > 6 mm in length. Whales initially foraged for amphipods along the 20‐m depth contour line; amphipod biomass was best developed and least variable at depths between 16 and 20 m.